The prince and the pauper - Twain, Mark 1835-1910.; Bogart, Shirley (New York Baronet Books, 1992)
When young Edward VI of England and a poor boy who resembles him exchange places, each learns something about the other's very different station in life.
Keywords: Edward -- VI -- King of England -- 1537-1553 -- Juvenile fiction; Edward -- VI -- King of England -- 1537-1553 -- Fiction; Mistaken identity -- Fiction; Adventure and adventurers -- Fiction; England -- Fiction